Revitalization of Istihsan Bi Al 'Urfi in Sharia Financing: Fatwa Study 2010-2018 - Mukri, Syarifah Gustiawati; Harisah, H; Shapiulayevna, Aliyeva Patimat (Journal of Islamic Economic Laws, 2023)
The community's need for sharia financing transactions is very urgent. So Islamic law products are required to be able to provide guidelines for community economic transactions as a form of response to community needs. From this, this study examines how the concept of istihsan bi al 'urfi was revitalized in one fatwa from 49 fatwas set by the DSN-MUI during the 2010-2018 period as evidence for legal determination. Therefore, istihsan bi al 'urfi is a form of ijtihad scholars in establishing law. The research method used is a qualitative research method with a literature approach, namely by observing the use of the determination method with istihsan bi al 'urfi. The results of the study stated that there was 13 times the use of istihsan bi al 'urfi in determining the permissibility of financing based on sharia as a legal consideration. Although previously it was equipped with arguments from the Qur'an and hadith as well as ijma' and qiyas. This shows that DSN-MUI ijtihad always develops according to the demands of the times to develop Islamic legal products in the field of Islamic finance and economics without losing the basic values of sharia.